The problems of using of deposits as a measure of restraint in criminal procedure of the Republic of Kazakhstan. (Journal of actual problems of jurisprudence, 2018)
The article considers the collision of two legislations acts: the code of criminal procedure and the instructionof application of pledge and home arrest as preventive punishment, and also the cause of preventing theusage of pledge in criminal process of the Republic of Kazakhstan.Keywords: deposit, a measure of restraint, prosecuting agency, property.